2018
DOI: 10.1038/mi.2017.89
|View full text |Cite
|
Sign up to set email alerts
|

Induction of vaginal-resident HIV-specific CD8 T cells with mucosal prime–boost immunization

Abstract: Tissue-resident memory (T) CD8 T cells survey a range of non-lymphoid mucosal tissues where they rapidly mediate clearance of viral infections at the entry portals. Vaccines that establish CD8 T cells in the cervicovaginal mucosa hold promise for effective immunity against sexually transmitted HIV. We demonstrate that HIV-specific CD8 T cells can be established in the murine vaginal mucosa using a combined intranasal and intravaginal mucosal immunization with recombinant influenza-HIV vectors. Using in situ te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 67 publications
4
39
0
Order By: Relevance
“…92 The activation of HIV-specific CD8 + T RM cells results in the recruitment of both adaptive and innate immune cells in the VM. 88 On the other hand, T RM cells can lyse infected target cells directly (Fig. 1).…”
Section: Cd8 + T Rm Cells In Anti-viral Immunitymentioning
confidence: 99%
See 2 more Smart Citations
“…92 The activation of HIV-specific CD8 + T RM cells results in the recruitment of both adaptive and innate immune cells in the VM. 88 On the other hand, T RM cells can lyse infected target cells directly (Fig. 1).…”
Section: Cd8 + T Rm Cells In Anti-viral Immunitymentioning
confidence: 99%
“…25 In the respiratory tract, T RM cells may confer protective immunity against viruses such as RSV, 80,85 Sendai virus, 86 and influenza. 36,73,87,88 High levels of lung-resident T RM cells are induced by administration of the mucosal Sendai virusengineered recombinant anti-TB vaccine (SeV85AB), which leads to a rapid and strong recall response against Mtb challenge infection. 89 Generation of T RM cells by intranasal vaccination of RSV antigen-expressing MCMV results in earlier T cell responses and viral clearance after RSV challenge.…”
Section: Cd8 + T Rm Cells In Anti-viral Immunitymentioning
confidence: 99%
See 1 more Smart Citation
“…This is done, for instance, by topical delivery of vaccine vectors, which results in T cell activation by dendritic cells in lymphoid tissues draining the site of application, followed by T cell migration to the mildly inflamed target tissue and subsequent formation of CD8 + CD103 + T RM cells. Examples such approaches include cervico‐vaginal immunization with papilloma virus vectors encoding model antigens, such as M/M2 from respiratory syncytial virus (RSV) or glycoproteins B and D from HSV, as well as combined intranasal and intravaginal immunization with IAV vectors expressing HIV p24 . Protective T RM cells in genital mucosa have also been generated by combined topical application of inactivated Chlamydia trachomatis elementary bodies with charge‐switched synthetic adjuvant particles .…”
Section: Trm Cells Orchestrate Immediate Local Immunitymentioning
confidence: 99%
“…[165] In a mouse study, they demonstrated that immunization with recombinant influenza-HIV vectors via combination intranasal and intravaginal administration resulted in localization of HIV-specific tissue-resident memory CD8 T cells in the vaginal mucosa. [166] Another study involving rhesus macaques, published in 2018, showed that combination adenovirus and protein vaccines were effective in increasing protection in intrarectal challenges. [167] Af-ter three intrarectal challenges, all the ten controls were infected, while only three and four out of ten were infected in the two respective vaccinated macaque groups.…”
Section: Hiv Vaccinesmentioning
confidence: 99%